2015
DOI: 10.1021/acs.biomac.5b01066
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Chelating Polymers (MCPs) with Zwitterionic Pendant Groups Complexed to Trastuzumab Exhibit Decreased Liver Accumulation Compared to Polyanionic MCP Immunoconjugates

Abstract: Metal-chelating polymers (MCPs) can amplify the radioactivity delivered to cancer cells by monoclonal antibodies or their Fab fragments. We focus on trastuzumab (tmAb), which is used to target cancer cells that overexpress human epidermal growth factor receptor 2 (HER2). We report the synthesis and characterization of a biotin (Bi) end-capped MCP, Bi-PAm(DET-DTPA)36, a polyacrylamide with diethylenetriaminepentaacetic acid (DTPA) groups attached as monoamides to the polymer backbone by diethylenetriamine (DET)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…The BCP employed in this study consists of an outer PEG block that provides “stealth” properties for in vivo applications 32 and an inner poly(glutamic acid) (PGlu) block that introduces functional groups for the conjugation of metal-chelating diethylenetriaminepentaacetic acid (DTPA) for future applications in radiotherapy ( Scheme 1 ). 33 As a proof-of-concept evaluation of their potential as imaging agents, the penetration properties of these BCP–CNCs were investigated in a 3D multicellular tumor spheroid (MCTS) model of ovarian cancer. Overall, the findings of this study demonstrate that the “grafting-to” method of CNC modification offers a robust platform for the preparation and characterization of BCP–CNC conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…The BCP employed in this study consists of an outer PEG block that provides “stealth” properties for in vivo applications 32 and an inner poly(glutamic acid) (PGlu) block that introduces functional groups for the conjugation of metal-chelating diethylenetriaminepentaacetic acid (DTPA) for future applications in radiotherapy ( Scheme 1 ). 33 As a proof-of-concept evaluation of their potential as imaging agents, the penetration properties of these BCP–CNCs were investigated in a 3D multicellular tumor spheroid (MCTS) model of ovarian cancer. Overall, the findings of this study demonstrate that the “grafting-to” method of CNC modification offers a robust platform for the preparation and characterization of BCP–CNC conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…The zwitterionic metal-chelating polymers exhibit enhanced biodistribution, increased blood levels of radioactivity, decreased absorption by normal tissue, and increased tumour uptake. Using the extracellular domain of HER2, surface plasmon resonance investigations examined that the MCP immune conjugates retain excellent antigen binding, with dissociation constants in the low nM range ( Liu et al, 2015 ). Using a fluorescein isothiocyanate/neutravidin receptor as an intermediate, a biotin end group enabled conjugation to biotinylated beads.…”
Section: Classification Of Orthopaedic Biomaterials and The Issuesmentioning
confidence: 99%
“…It was shown that the attachment of the MCP to the trastuzumab-streptavidin conjugates had no significant effect on the rate of binding to the extracellular domain of HER2 or the dissociation rate (the interaction was characterized by a low nanomolar binding constant). The biodistribution and micro SPECT/CT (single-photon emission computed tomography/computed tomography) imaging studies on Balb/C mice showed that the tissue distribution of the trastuzumab Fab-streptavidin-MCP conjugates was dependent on both the chemical structure of the polymer backbone and the nature of the pendant group to which the DTPA units were attached [43]. Rapid elimination from the blood and high liver uptake have been found to be related to the polyanionic character of the MCP.…”
Section: Organic Nanocarriersmentioning
confidence: 99%